(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The Rupelian Uromieh section of the Qom Formation was analyzed with the aim to provide a first description of its coralline algal assemblages, and benthic paleoenvironmental evolution through time. The presence of Nummulites fichteli, Nummulites vascus, Halkyardia maxima and Subterraniphyllum thomasii, together with the absence of Nephrolepidina and Eulepidina confirm an early to middle Rupelian age. In the lower part of the section, the abundance of miliolids and corals suggests a proximal inner-platform environment, while upsection the increase in large rotaliids, coralline algae and bryozoans points toward a distal inner-platform/proximal middle-platform setting. Coralline algal assemblages support this interpretation, with Sporolithales and Hapalidiales becoming more common in the upper part of the section. Within the coralline assemblage, Lithoporella melobesioides and Titanoderma pustulatum are two of the most common species, together with articulated coralline algae. S. thomasii is more common in coral-rich intervals, confirming that the distribution of this species was confined to shallow-water environments. The specimens of T. pustulatum recovered in the Uromieh section predate all the other known records of this species, indicating that the origin of T. pustulatum should be dated at least at the early Rupelian